Model Bimbingan Konseling Islam Dalam Membentuk Karakter Sufistik Santri Era Revolusi Industri Generasi Keempat - Fithriyah, Imaniyatul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
Era of industrial revolution 4.0 or the fourth generation has an impact on the world of education including in islamic boarding school both positive and negative, this can easily be obtained and accessed by individuals without knowing the original of the information which can lead to slander and panic to others. The ease of accessing information without knowing the truth will give rise to false news (hoaxes) which need to be anticipated so as not to cause disputes between communities both in cyberspace and the real world. This is not just how to reduce access to information, but more essential, namely to make individuals aware of the importance of providing guidance with a sufistic approach. The world of education has become the front line in improving the sufistic character of student so that they are able to adapt and adapt to the potential of the 21st century. The purpose of writing this article is to reconstruct Islamic guidance and counseling models in shaping the sufistic character of students in the era of industrial revolution 4.0. The method used in this writing is qualitative with the type of theoretical-descriptive research based on library research. The results of this study are Islamic guidance and counseling model can form the sufistic character of students by giving assistance to the counselee or student in order to develop all his disposition to deal with the problem in accordance with the guidance of Islamic teachings, in the sense that the counselee or student are able to live in harmony with Allah SWT provisions and instructions, namely; a) in harmony with Allah nature, in harmony with the sunnatullah, in harmony with its nature as a creature of Allah; b) in harmony with the guidelines determined by Allah through His Messenger; c) realize its existence as a creature of Allah created to worship or serve Allah in the broadest sense.